Rate of Return on Equity: Third Party Funds, Problem Finance, and Operational Efficiency at Indonesian Sharia Bank - Listya Sugiyarti; Nur Asmilia; Siti Hanah (Monex: Journal of Accounting Research, 2023)
This study seeks empirical evidence of the relationship between third-party funding, non-performing loans, and operational efficiency and the rate of capital return for Islamic Commercial Banks in Indonesia from 2014 to 2018. This study's population consists of Islamic Commercial Banks registered with the Financial Services Authority in Indonesia. For the sample, this study used a form of purposive sampling. This methodology yielded a sample of eleven Islamic commercial banks. Using descriptive statistics, the classical assumption test, hypothesis testing, and multiple linear regression, this study tests its hypotheses. According to the findings of this study, the rate of return on equity in Islamic Commercial Banks is significantly influenced by third-party funding, non-performing financing, and operational efficiency. While third party funds partially have no effect and are not significant on the rate of return on capital at Islamic Commercial Banks, non-performing financing has a major impact on both the rate of return on capital and operational efficiency of Islamic Commercial Banks